A fast-rotator post-starburst galaxy quenched by supermassive black-hole feedback at z = 3 - D’Eugenio, F; Pérez-González, PG; Maiolino, R; Scholtz, J; Perna, M; Circosta, C; Übler, H; Arribas, S; Böker, T; Bunker, AJ; Carniani, S; Charlot, S; et al. (Nature Research, 2024)
The most massive galaxies in the Universe stopped forming stars due to the time-integrated feedback from central supermassive black holes (SMBHs). However, the exact quenching mechanism is not yet understood, because local massive galaxies were quenched billions of years ago. Here we present JWST/NIRSpec integral-field spectroscopy observations of GS-10578, a massive, quiescent galaxy at redshift z = 3.064 ± 0.002. From its spectrum, we measure a stellar mass M⋆ = 1.6 ± 0.2 × 1011 M⊙ and a dynamical mass Mdyn = 2.0 ± 0.5 × 1011 M⊙. Half of its stellar mass formed at z = 3.7–4.6, and the system is now quiescent, with a current star-formation rate of less than 19 M⊙ yr−1. We detect ionized- and neutral-gas outflows traced by [O iii] emission and Na i absorption, with mass outflow rates 0.14–2.9 and 30–100 M⊙ yr−1, respectively. Outflow velocities reach vout ≈ 1,000 km s−1, comparable to the galaxy escape velocity. GS-10578 hosts an active galactic nucleus, evidence that these outflows are due to SMBH feedback. The neutral outflow rate is higher than the star-formation rate. Hence, this is direct evidence for ejective SMBH feedback, with a mass loading capable of interrupting star formation by rapidly removing its fuel. Stellar kinematics show ordered rotation, with spin parameter λRe=0.62±0.07, meaning GS-10578 is rotation-supported. This study presents direct evidence for ejective active galactic nucleus feedback in a massive, recently quenched galaxy, thus helping to clarify how SMBHs quench their hosts. The high value of λRe implies that quenching can occur without destroying the stellar disk.